Multiplex PCR Detection of Common Carbapenemase Genes and Identification of Clinically Relevant Escherichia coli and Klebsiella pneumoniae Complex - Rujirat Hatrongjit; Peechanika Chopjitt; Parichart Boueroy; Anusak Kerdsin (MDPI AG, 2022)
Carbapenem-resistant Enterobacterales (CRE) species are top priority pathogens according to the World Health Organization. Rapid detection is necessary and useful for their surveillance and control globally. This study developed a multiplex polymerase chain reaction (mPCR) detection of the common carbapenemase genes NDM, KPC, and OXA-48-like, together with identification of Escherichia coli, and distinguished a Klebsiella pneumoniae complex to be K. pneumoniae, K. quasipneumoniae, and K. variicola. Of 840 target Enterobacterales species, 190 E. coli, 598 K. pneumoniae, 28 K. quasipneumoniae, and 23 K. variicola. with and without NDM, KPC, or OXA-48-like were correctly detected for their species and carbapenemase genes. In contrast, for the Enterobacterales species other than E. coli or K. pneumoniae complex with carbapenemase genes, the mPCR assay could detect only NDM, KPC, or OXA-48-like. This PCR method should be useful in clinical microbiology laboratories requiring rapid detection of CRE for epidemiological investigation and for tracking the trends of carbapenemase gene dynamics.